A disciplina normativa brasileira sobre a intimidade e os bancos de dados - Marco Aurélio Rodrigues da Cunha e Cruz (Araucaria)
The right to privacy in the age of information is a relatively recent theme, that does not lose this characteristic. The collect and storage of personal data became a custom in contemporary States, resulting in the creation of the several databases. The possibility of an illegitimate use of the individual is information motivated the discussion of a new dimension of state protection of the right to privacy: the right to informative self-determination. What is extracted of the done research is that although there is not a Brazilian specific law to be in charge of protecting the right to privacy, the citizen can be aided by scattered norms.